Shape Memory of Elastic Capsules Under the Effect of Spontaneous Shape (Communications in Computational Physics, 2018)
Red blood cells can recover their resting shape after having been deformedby shear flow. Their rims are always formed by the same part of the membranes, andthe cells are said to have shape memory. Modeled as two-dimensional elastic capsules,their recovery motion and shape memory is studied, mainly focused on the effect of thespontaneous shape. The fluid-structure interaction is modeled using immersed boundarymethod. Based on the simulations, the resting shapes of capsules are obtained andthe area ratio of spontaneous shape is found to play an important role. After removeof shear flow, all capsules can recover their resting shapes, while only capsules withnoncircular spontaneous shapes present shape memory. As the spontaneous shapeapproaches a circle but still noncircular, the capsule spends more time on recoveryprocess. We consider how these capsules deform depending on the membrane bendingenergy, and find that the relaxation speed is positive correlated to the range ofvalues of dimensionless bending energy. These results may help to identify differentspontaneous shapes for capsules especially RBCs through future experiments.
Keywords: Fluid-structure interaction; immersed boundary method; shape memory; spontaneous shape.